The Influence of Audit Tenure, Audit Fee, Auditor Reputation, and Client Company Size on Audit Quality - Fernandez, Stephanie; Chan, Keline Ricca; Salim, Kevin; Sitepu, Wilsa Road Betterment; Simanjuntak, Owen de pinto (International Journal Of Economics Social And Technology (IJEST), 2024)
Audit quality is the most important consideration for users of audit reports because an assessment of the audit opinion by investors and potential investors will be provided. The opinion received will also not be qualified if the audited financial statements are not audited by an auditor who has audit quality, and the size of the company will not affect the quality of the audit. Thus, bad decisions can be taken by report users. Therefore, this research aims to examine the influence of audit quality on audit tenure, audit fees, auditor reputation, and client company size. The population that is the focus of the research is all manufacturing companies listed on the Indonesia Stock Exchange in the 2019-2021 period. Sampling was carried out using quantitative descriptive methods, and based on established criteria, there were 67 manufacturing companies in the sample with an observation period of 3 years. Thus, the final sample size is 201. The research results state that audit tenure has no impact on audit quality, audit fees have no impact on audit quality, and auditor reputation also has no impact on audit quality